Histórias da Amazônia na educação básica: o que nos contam os conteúdos? - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This case study investigates which representations of the Amazon are being presented in basic education in Santarém-PA. The research was developed in a municipal elementary school located in the central area of the city. The methodology of this investigation was carried out through documentary sources, which are the didactic materials and course plan of the Amazonian Studies discipline, in addition to an interview with the teacher who teaches this curricular component. The curricular component emerged at the end of the 20th century; however, narratives of absence and/or lack of Amazonian studies content are constant, as well as the notable connection of this fact with the lack of regional and local historical awareness among many students and teachers contacted. This study found in the pages of the didactic materials regional and local content that supports a history teaching capable of contributing to the construction of critical and reflective historical awareness, connected from the local to the global.This case study investigates which representations of the Amazon are being presented in basic education in Santarém-PA. The research was developed in a municipal elementary school located in the central area of the city. The methodology of this investigation was carried out through documentary sources, which are the didactic materials and course plan of the Amazonian Studies discipline, in addition to an interview with the teacher who teaches this curricular component. The curricular component emerged at the end of the 20th century; however, narratives of absence and/or lack of Amazonian studies content are constant, as well as the notable connection of this fact with the lack of regional and local historical awareness among many students and teachers contacted. This study found in the pages of the didactic materials regional and local content that supports a history teaching capable of contributing to the construction of critical and reflective historical awareness, connected from the local to the global.
Keywords: História da Amazônia.; Material didático; História Regional e Local; Ensino de História; CNPQ:: CIÊNCIAS HUMANAS